Molecular Epidemiology and Colistin-Resistant Mechanism of mcr-Positive and mcr-Negative Escherichia coli Isolated From Animal in Sichuan Province, China - Li, Fulei; Cheng, Ping; Li, Xiaoting; Liu, Ruimeng; Liu, Haibin; Zhang, Xiuying (Frontiers in Microbiology, 2022)
Colistin is the last line of defense in the treatment of multidrug-resistant Gram-negative bacterial infections. However, colistin resistance is increasing worldwide, with resistance commonly regulated by two-component systems and plasmid-mediated. Therefore, this study aimed to investigate the chromosome-mediated and plasmid-mediated colistin resistance in Escherichia coli isolates from animals (Chicken, Pig, Cattle, and Dog) in Sichuan Province, China. In total, 300 fecal samples from animals were selected. PCR was used to detect the different MCR variants (MCR-1~MCR-9) and MLST was used for strain typing of thirty MCR-1 positive isolates. Thirty MCR-1-negative isolates were selected from a collection of colistin-resistant E. coli isolates to investigate amino acid alterations in PmrAB, PhoPQ, and mgrB. SMART analysis was performed to determine the domain architectures of PmrA, PmrB, PhoP, PhoQ, and mgrB. 101 colistin-resistant isolates, the MCR gene was detected in 58 out of 101 isolates. Thirty MCR-1 positive E. coli isolates were classified into 17 sequence types, ST10 (6/30, 20.0%) was the most common ST among the 30 MCR-1 positive isolates, followed by ST206 (n = 3, 10.0%), ST48 (n = 3, 10.0%), ST155 (n = 3, 10.0%), ST542 (n = 2, 6.7%), ST2539 (n = 2, 6.7%), and then by single ST type isolates. The conjugation experiment and plasmid replicon type analysis suggest that the MCR-1 gene was primarily localized on an IncX4-type and IncI2 plasmid. Twenty-eight MCR-1-negative colistin-resistant E. coli isolates carried diverse amino acid alterations in PmrA, PmrB, PhoP, PhoQ, and/or mgrB, whereas no mutation in any of these genes was found in the remaining isolates. Mutations have occurred in different domains of both PmrA and PmrB. Additionally, PmrA appears to be the most commonly mutated gene in E. coli. The findings of this study demonstrated the high prevalence of colistin in farms in Sichuan, China. The conjugation experiment and plasmid replicon type analysis suggest that the MCR-1 gene was primarily localized on an IncX4-type and IncI2 plasmid. In our study demonstrates colistin resistance of MCR-negative isolates is related to chromosomal point mutations including the two-component systems PhoP/PhoQ and PmrA/PmrB, and their regulators MgrB